2006
DOI: 10.1007/s10101-005-0008-2
|View full text |Cite
|
Sign up to set email alerts
|

Corruption, Growth, and Income Distribution: Are there Regional Differences?

Abstract: Corruption, Degenerative corruption, Growth, Income inequality, Regional differences, Panel data, Africa, Asia, Latin America, Oecd, O1, O55, C33,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
55
0
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(70 citation statements)
references
References 29 publications
7
55
0
8
Order By: Relevance
“…Gyimah-Brempong [43] examined the effect of corruption on income inequality in selected African countries, and reported that higher corruption had an adverse effect on the income distribution. Further, Gyimah-Brempong and de Camacho [44] pointed out that the 'degenerative' nature of corruption practiced typically in African and Latin American countries has a much more deleterious effect on the income distribution, compared to the 'developmental' corruption found in Asia.…”
Section: The Relationship Between Institutions and Inequalitymentioning
confidence: 99%
See 2 more Smart Citations
“…Gyimah-Brempong [43] examined the effect of corruption on income inequality in selected African countries, and reported that higher corruption had an adverse effect on the income distribution. Further, Gyimah-Brempong and de Camacho [44] pointed out that the 'degenerative' nature of corruption practiced typically in African and Latin American countries has a much more deleterious effect on the income distribution, compared to the 'developmental' corruption found in Asia.…”
Section: The Relationship Between Institutions and Inequalitymentioning
confidence: 99%
“…Gyimah-Brempong and de Camacho [44] concluded that improvements in institutional quality were associated with falling income inequality. However, Andres and Ramlogan-Dobson [21], Chong and Caldéron [14], and Li et al [45] claimed that there could be a trade-off between such improvements and income inequality in developing countries.…”
Section: Inequality Growth and Institutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Marginal positive impacts are characteristics of countries with substantial institutional deficiency (Méon & Weill, 2010;Aidt, 2009;Aidt et al, 2008;Houston, 2007). 3 See, amongst others: Li et al (2000), Gymiah-Brempong (2002), Gupta et al (2002), You and Khagram (2005), Gyimah-Brempong et al (2006) and Dincer and Gunalp (2008).…”
Section: Introductionmentioning
confidence: 99%
“…The ramifications can be comprehensive and handicap progress, affecting economic development, political efficacy, and social stability. Several scholars highlight corruption as a primary cause for underdevelopment (Alam, 1989;Macrae, 1982;O'Higgins, 2006;Theobald, 1999) while others point to corruption as the leading reason for stagnant economies (GyimahBrempong & Munoz de Gyimah-Brempong, 2006;Sandbrook, 1986;Warren, 2004). I argue that corruption, whether experienced or perceived, impacts the population's satisfaction with democracy and its values, eroding trust in government and formal political structures.…”
mentioning
confidence: 99%